An adaptive approach for ship heave and horizontal motion compensation based on GEO satellite/airborne bistatic SAR. Issue 9 (2nd September 2018) - Jiang, Yicheng; Lian, Meng
ABSTRACT: Geosynchronous satellite/airborne bistatic synthetic aperture radar (GEO SA-Bi SAR), which employs a geosynchronous orbit (GEO) satellite as a transmitter and an airplane that works on the 'receive-only' mode as a receiver, is considered for marine surveillance. The heave and horizontal motion of ship target which caused by wave and propulsion respectively are compensated, using a combination of adaptive notch filtering (ANF), root multiple signal classification (Root-MUSIC) and linear least squares algorithm. The correctness and effectiveness of this approach is demonstrated by the simulation results.